Childhood leukaemia in the West Berkshire and Basingstoke and North Hampshire District Health Authorities in relation to nuclear establishments in the vicinity. Issue 6572 (7th March 1987) - Roman, E; Beral, V; Carpenter, L; Watson, A; Barton, C; Ryder, H; Aston, D L
Abstract : During the years 1972-85, 89 children aged 0-14 were registered with leukaemia in the West Berkshire and Basingstoke and North Hampshire District Health Authorities. Two nuclear establishments are located within the health authorities, and a third is situated nearby. Fifty of the 143 electoral wards in the two district health authorities lie wholly within, or have at least half their area lying within, a circle of radius 10 km around the establishments. In those 50 electoral wards 41 children aged 0-14 were registered with leukaemia, 28.6 registrations being expected on the basis of leukaemia registration rates in England and Wales (incidence ratio = 1.4, p less than 0.05). This excess was confined to children aged 0-4, among whom there were 29 registrations of leukaemia, 14.4 being expected (incidence ratio = 2.0, p less than 0.001). In the remaining 93 electoral wards there was a small and non-significant increase in the number of registrations of leukaemia at age 0-14 (48 observed, 40.8 expected; incidence ratio = 1.2). There was no obvious trend in the incidence of childhood leukaemia over the 14 years and the overall occurrence of the malignancy in the 143 electoral wards was consistent with a random distribution. In the surrounding Oxford and Wessex Regional Health Authorities the number of registrations of leukaemia at age 0-14 was virtually identical with that expected on the basis of registration rates in England and Wales (362 observed, 372.5 expected; incidence ratio = 1.0). These data indicate that in the two district health authorities studied there was an excess incidence of childhood leukaemia during 1972-85 in the vicinity of the nuclear establishments. In the West Berkshire and Basingstoke and North Hampshire District Health Authorities an average of 60, 000 children aged 0-14 lived within a 10 km radius of a nuclear establishment each year. The normal expectation of leukaemia in these children was two cases a year, whereas the recorded incidence was three cases per year, representing one extra case of leukaemia each year among these 60, 000 children.